Imprinting of distal mouse chromosome 2 is associated with phenotypic anomalies in utero - WILLIAMSON, CHRISTINE M.; BEECHEY, COLIN V.; PAPWORTH, DAVID; WROE, STEPHANIE F.; WELLS, CHRISTINE A.; COBB, LEON; PETERS, JOSEPHINE (Genetical Research, 1998)
Previous studies have shown that the distal region on mouse chromosome (Chr) 2 is subject to imprinting as mice with maternal duplication/paternal deficiency (MatDp.dist2) and the reciprocal (PatDp.dist2) for this region exhibit phenotypic anomalies at birth and die neonatally. We show here that imprinting effects are detectable in utero. Notably PatDp.dist2 embryos show an increase in wet weight compared with normal, which peaks at 16·5 d post coitum (dpc), and diminishes by birth, whereas the wet weight of placenta is slightly reduced in the latter half of gestation. Newborns have increased length of the long bones. By contrast, the wet weight of MatDp.dist2 embryos decreases during the second half of gestation. Measurements of dry weights of embryos at 16·5 dpc have indicated that there is no difference in either PatDp.dist2 or MatDp.dist2 compared with normal so that the wet weight differences are due to fluid retention in PatDp.dist2 but fluid loss in MatDp.dist2. In PatDp.dist2 embryos excess fluid is particularly prominent in the subcuticular skin layer, whereas by birth fluid is evident around the neck and tongue. At 16·5 dpc the PatDp.dist2 embryos are severely oedematous, as the average fluid content per unit dry weight per embryo was increased by 40%, whereas the MatDp.dist2 embryos are dehydrated as the average water content per unit dry weight per embryo was reduced by 6%. A preliminary conclusion is that there is neither growth enhancement in PatDp.dist2 nor growth retardation in MatDp.dist2 offspring.